Erosion of the Alberta badlands produces highly variable and elevated heavy metal concentrations in the Red Deer River, Alberta - Kerr, Jason G.; Cooke, Colin A. (The Science of the total environment, 2017)
Erosion is important in the transport of heavy metals from terrestrial to fluvial environments. In this study, we investigated riverine heavy metal (Cd, Cu, Hg and Pb) dynamics in the Red Deer River (RDR) watershed at sites upstream (n=2) and downstream (n=7) of the Alberta badlands, an area of naturally high erosion. At sites draining the badlands, total water column Cd, Cu, Hg and Pb concentrations frequently exceeded guidelines for the protection of freshwater biota. Furthermore, peak concentrations of total Cd (9.8μgL−1), Cu (212μgL−1), Hg (649ngL−1) and Pb (361μgL−1) were higher than, or comparable to, values reported for rivers and streams heavily impacted by anthropogenic activities. Total suspended solids (TSS) explained a large proportion (r2=0.34–0.83) of the variation in total metal concentrations in the RDR and tributaries and metal fluxes were dominated by the particulate fraction (60–98%). Suspended sediment concentrations (Csed) and metal to aluminum ratios were generally not indicative of substantial sediment enrichment. Rather, the highly variable and elevated metal concentrations in the RDR watershed were a function of the high and variable suspended sediment fluxes which characterize the river system. While the impact of this on aquatic biota requires further investigation, we suggest erosion in the Alberta badlands may be contributing to Hg-based fish consumption advisories in the RDR. Importantly, this highlights a broader need for information on contaminant dynamics in watersheds subject to elevated rates of erosion. [Display omitted] •Erosion of contaminated soil is a major cause of riverine heavy metal contamination.•Examined riverine heavy metal dynamics in a highly erosive watershed.•No evidence of widespread enrichment of suspended sediments with heavy metals.•Elevated riverine heavy metal concentrations due to high instream sediment mass.•Erosion of ‘background’ soils produced levels typical of heavily impacted rivers.